The Visigoths in Gaul and Iberia - Ferreiro, Alberto, author.
1 online resource.
Keywords: The bibliography includes material published from 1984 to 2003. The historical chronology has been expanded to include the fourth century. This includes unlike the first one Iberian Fathers such as Gregory of Elvira, Potamius of Lisboa, Prudentius, and Pacian of Barcelona. As with the first bibliography (Brill, 1988) among the many topics represented are: Archaeology, Liturgy, Monasticism, Iberian-Gallic Patristics, Paleography, Linguistics, Germanic and Muslim Invasions, and more. In addition, peoples such as the Vandals, Sueves, Basques, Alans and Byzantines are included. The book contains author and subject indexes and is extensively cross-indexed for easy consultation. A periodicals index of hundreds of journals accompanies the volume. This collection of nearly 8,000 entries is an attempt to bring up-to-date the scholarship on Iberia and Gaul in Late Antiquity.